Price discovery in dual‐class shares across multiple markets. Issue 1 (28th November 2017) - Fernandes, Marcelo; Scherrer, Cristina M.
Abstract : This paper proposes a new measure of price discovery that uses the spectral decomposition. The methodology is especially important in the context of large price systems, such as interest rate parities with spot and futures contracts or dual‐class shares in multiple markets. We employ high frequency data to study price discovery in dual‐class Brazilian stocks and their ADRs. We find that the foreign market is at least as informative as the home market and that shocks in the dual‐class premium entail a permanent effect in normal times, but transitory in periods of financial distress